2018
DOI: 10.3348/kjr.2018.19.4.704
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Three-Dimensional Navigator-Gated Whole-Heart MRI and Two-Dimensional Cine MRI in Quantifying Ventricular Volumes

Abstract: ObjectiveTo test whether the method utilizing three-dimensional (3D) whole-heart MRI has an additional benefit over that utilizing conventional two-dimensional (2D) cine MRI in quantifying ventricular volumes.Materials and MethodsIn 110 patients with congenital heart disease, a navigator-gated, 3D whole-heart MRI during end-systole (ES) and end-diastole (ED), 2D short-axis cine MRI, and phase contrast MRI of the great arteries were acquired. Ventricular volumes were measured by using a 3D threshold-based segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
(64 reference statements)
2
13
0
Order By: Relevance
“…Other researchers have suggested that volumetric quantification using a 3D imaging modality may expedite a better understanding of the relationship between the RV status and disease severity in Ebstein anomaly [4,5]. In particular, the use of 3D threshold-based segmentation could eliminate the time-consuming and reader-dependent manual endocardial tracings for ventricular volumetry as demonstrated in previous studies [7,9]. The threshold-based approach was reported to show high reproducibility with an inter-measurement difference of 1.0±1.1%, and intraclass correlation coefficient of 1.0 [24].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Other researchers have suggested that volumetric quantification using a 3D imaging modality may expedite a better understanding of the relationship between the RV status and disease severity in Ebstein anomaly [4,5]. In particular, the use of 3D threshold-based segmentation could eliminate the time-consuming and reader-dependent manual endocardial tracings for ventricular volumetry as demonstrated in previous studies [7,9]. The threshold-based approach was reported to show high reproducibility with an inter-measurement difference of 1.0±1.1%, and intraclass correlation coefficient of 1.0 [24].…”
Section: Discussionmentioning
confidence: 91%
“…However, cine MRI is limited by its ability to accurately segment the malformed tricuspid valve and RV endocardial borders because of its two-dimensional (2D) nature [3][4][5][6].Cardiac MRI is generally limited by its long examination time, which often requires conscious sedation or general anesthesia. In addition, the threshold-based segmentation results of threedimensional (3D) whole-heart MRI data are often influenced by inhomogeneous signal intensity and imaging artifacts [7]. In contrast, cardiac CT is increasingly used to evaluate congenital cc This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (https://creativecommons.org/licenses/bync/4.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.Objective: The purpose of this study was to demonstrate the feasibility of using cardiac CT to perform volumetric severity assessment of the Ebstein anomaly.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we offer a practical standard CMR protocol for beginners designed to be easy to follow and implement. This protocol guideline is based on previously reported CMR guidelines [1][2][3][4][5][6][7][8][9] and includes sequence terminology used by vendors, essential MR physics [10][11][12][13][14][15][16][17], imaging planes [2,18], field strength considerations [19][20][21][22][23][24][25], MRI-conditional devices [10,20,[26][27][28][29][30][31][32][33], drugs for stress tests [34], various CMR modules [16,[35][36][37][38][39][40][41][42][43][44][45]…”
Section: Introductionmentioning
confidence: 99%
“…The anatomy and cardiac function section includes cine magnetic resonance imaging (MRI), flow imaging, and angiography. Cine MRI has been known as the gold standard for ventricular functional analysis and, with recent advances in MRI and CT, studies comparable to cine MRI have been reported [4][5][6]. In addition, studies have been carried out to estimate the prognosis of the disease by measuring myocardial strain using cine MRI, and to evaluate the left atrial volume in patients with atrial fibrillation by using three-dimensional (3D) CMR [7][8][9].…”
Section: Introductionmentioning
confidence: 99%